Análise do conforto ambiental em salas de aula da Universidade Federal de Goiás - Ochoa, Juliana Herlemann (2010)
Provide users good physical conditions in educational institutions is essential for the proper development of teaching and learning. This work deals with the verification in-loco of the environmental comfort of classrooms in two buildings with different architectural and construction techniques, that are part of the structure of the Federal University of Goiás. So the research aimed at exploring these buildings in order to identify the peculiarities of its thermal, acoustic and light performance which are being influenced by the technologies adopted and the physical conformation of the same. The technical data collected were analyzed by type of comfort. In lighting comfort, measurements were carried out near the solstices and equinoxes and the data collected were analyzed by means of ambient illuminance, uniformity coefficient and contribution of artificial light. The thermal comfort data collected were temperature and relative humidity for a period of approximately 11 months, which were assessed using the concept of comfort zone, degree-hours analysis and absolute maximum and minimum values. The acoustic measurements collected the sound pressure levels and occurred over a day of daily activities in both buildings. It was noted that there is an influence of the architectural elements of environmental comfort in buildings. Among other factors, one that can be highlighted is that despite having similar solar orientation, which is a comfort condition, the results of the environmental performance of each of the buildings were quite different. Parallel to these technical assessments were also done a periodic application of questionnaires to the users of the classroom, one per season, which sought to characterize the perception of these in relation to each of the types of comfort. Finally, a correlation was established between the technical data collected and perceptive. In most of cases, the opinions expressed by users were not consistent with the results evaluated by measurement techniques, thus demonstrating a difference between the comfort zone adopted and the actual user satisfaction of the buildings.